Justice And Accuracy in Wage Payment from the Perspective of Islamic Economic Law: A Study of the Wage System of Rice Dryers in Brebes - Cahyani, Denti Tri; Sukron, Mokhamad (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2025)
Wage determination constitutes a fundamental aspect of labor relations, as it concerns the workers’ basic rights to fair compensation for services rendered. Nevertheless, wage systems frequently give rise to disputes, particularly regarding payment delays, unclear nominal values, and inconsistencies with the principle of justice. Such issues are evident in the wage practices of rice-drying laborers in the studied village, where employment agreements are made orally and wage payments depend on the sale of the dried rice. This phenomenon merits scholarly examination from the perspective of Islamic economic law, especially through the concept of ujrah, which emphasizes justice, contractual clarity, and timeliness in wage payment. This study employs a qualitative method with a juridical-empirical approach. Primary data were collected through in-depth interviews with rice mill owners, paddy owners, and rice-drying workers, complemented by direct field observations. Secondary data were derived from relevant literature on Islamic economic law and fiqh al-mu‘āmalah. The data were analyzed through reduction, presentation, and conclusion-drawing processes based on the principles of wage determination in Islamic law—justice, clarity of contract, mutual consent, and punctual payment. The findings reveal that the rice-drying wage system follows a piece-rate payment model, in which the wage amount is determined by the quantity of rice successfully dried. Payments are generally made after the rice is sold, which occasionally results in delayed disbursement. To mitigate such issues, rice mill owners provide cash advances (kasbon) for workers in urgent need of funds. From the standpoint of Islamic economic law, this practice largely aligns with the principles of contractual transparency and mutual consent, although improvements are needed in ensuring timely wage payment to prevent potential harm to workers.